An Anthropology of Images in the Education Sciences - Somogyvári, Lajos (Autonomy and Responsibility Journal of Educational Sciences, 2022)
My researches based upon the photographical corpus of the Hungarian periodical journals in the 1960’s. I have been examined six journals: Family and School (Család és Iskola), Our Child (Gyermekünk), Public Education (Köznevelés), Education in Kindergarten (Óvodai Nevelés), The Elementary Teacher (A Tanító) and The Work of the Elementary Teacher (A Tanító Munkája). In this interdisciplinary approach I combine the traditional sources of history of education with iconography and anthropology. Several sequences of pictures can be separate in this 5371 elements’ corpus – the main goal of my study is to draw the fi gures of the formal and informal education and the everyday history of the schooling. In this paper I try to give a short theoretical background to the work of photograph-analyses (the anthropology of images) in the history of education, and a brief example of the application of the research methodology.